Exploiting WiMAX for covert transmission of secret data over fading channel. (29th January 2020) - Kumar, Sanjeev; Kumar, Manoj; Singh, Amarpal
Summary: Worldwide Interoperability for Microwave Access (WiMAX) is the broadband wireless access technique that provides rapid broadband services to domestic and enterprise users. Owing to the broadcast characteristic of the WiMAX system, transmitted data security is crucial, particularly when the messages are confidential. In this work, exploiting of WiMAX to convey sensitive secret information is presented. In the first phase, we exploited conventional WiMAX (fast Fourier transform [FFT]‐WiMAX), and in the second phase, we propose a wavelet packet transform (WPT)–based WiMAX for covert communication. The quality evaluation of both covert transmission models (FFT‐WiMAX and WPT‐WiMAX) over the fading channel is done in this work. The experimental outcomes of the proposed WPT‐WiMAX covert transmission system reveal a significant enhancement in error rate (bit error rate) and peak signal‐to‐noise ratio for a given signal‐to‐noise ratio. Abstract : In this work, we exploit Worldwide Interoperability for Microwave Access (WiMAX) to transmit a covert secret data imperceptible to intruders. In the first phase, we exploited conventional WiMAX (fast Fourier transform [FFT]‐WiMAX), and in second phase, we propose wavelet packet transform (WPT)–based WiMAX for covert communication. The quality evaluation of both covert transmission models (FFT‐WiMAX and WPT‐WiMAX) over the fading channel is done in this work.